Gnosis and the Sexual Transgressive in Pat Barker's Regeneration Trilogy. Issue 1 (1st January 2016) - Bond, Christopher
Abstract: The homosexual orientation of three major characters in Pat Barker's The Regeneration Trilogy strengthens their mistrust for the prevailing rationale of the war. Ultimately, the antiwar stance of the trilogy's societally alienated, sexually transgressive characters is undermined by their return to combat. The motif of a single, enucleated eyeball links to the text's powerful theme of observation. The absolutely detached, impossible vision of an enucleated eye is required if the acknowledged futility of war is to have practical value.